Characteristic of Ceremai Fruit Electrical Properties as Electrolyte Solution in Galvanic Cells - Lalu Ahmad Didik Meiliyadi; Isniwana Damayanti; Amalia Syuzita (Postgraduate, University of Mataram, 2023)
It has been conducted a research to analyze ceremai fruit (Phyllanthus acidus) as an electrolyte solution for galvanic cells. The materials used consisted of copper (Cu), zinc (Zn) electrodes and an electrolyte solution from ceremai fruit. Electrolyte solution with a concentration variation of 60 to 100% was obtained from pure ceremai fruit electrolyte solution mixed with aquades. In addition, the electrolyte solution is fermented in a period of 1 to 5 days. The variables measured were pH, voltage, electric current and electric power. Based on the data analysis, it was found that the value of the acidity level was proportional to the concentration where at 100% solution concentration the pH value was 4.8 and at 60% the pH value was 5.4. The greatest voltage is 1 volt that obtained when the solution is in the most acidic state or highest concentration. It is found that the greater the concentration of the solution, the smaller the pH value (the acidity level increases) the value of the voltage, current and power will increase. However, when the electrolyte solution is fermented, it appears that the pH value is inversely proportional to the voltage generated. The longer of fermentation time, the pH value will increase but the voltage value will decrease. When the electrolyte solution is fresh, the pH value is 4.8 with a voltage of 1 volt, but on the 5th day of fermentation the acidity level increases with pH value of 2.15 but the voltage decreases to 0.65 volts. This is caused by oxygen exposure at the time of measurement so that the oxygen in the solution will increase. An increase of oxygen will reduce the density of electrically charged ions so that the current will decreases and the voltage will also decrease. Â